Sediment disposal in coastal waters - Zhao, Bing (2014)
Many coastal activities, like land reclamation and dredging, involve open-water sediment disposal, and are being conducted intensively around the world. It is essential to study the near-source sediment transport mechanism in order to guide engineering applications and minimize environmental impacts. The present study focused on instantaneous releases of sediment from a point source through laboratory experiments. Flow visualization, particle image velocimetry (PIV) and planar laser induced fluorescence (PLIF) techniques were adopted during the measurements. The internal density and velocity fields of single-phase miscible thermals, which could be considered as sediment clouds with infinitesimally small particle size, were first quantified, and the results helped to carry forward the understanding of unsteady buoyant convection flow in general. The two-phase characteristics were then investigated, and a numerical model was developed to simulate the motion of both solid and fluid phases. Two engineering factors, including air release heights and ambient waves, were also studied systematically and the results could be extended to field applications.